HIDDEN REGULARITY OF SOLUTION FOR A WAVE EQUATION WITH THE p-LAPLACIAN OPERATOR - Cabanillas Lapa, Eugenio (2013)
In this paper we study the hidden regularity of solutions for a wave equation with the p-laplacian operator...Indeed, we will prove that the normal derivative...